2021
DOI: 10.1016/j.jpeds.2021.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Study of Acute Liver Failure in Children Using Next Generation Sequencing Technology

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Although not generally considered as part of the first-line workup for acute liver failure, molecular testing is essential to confirm certain diagnoses in the pediatric population. 8,9 DNA sequencing technology (e.g., clinical exome sequencing and next generation sequencing) is increasingly effective in detecting inherited metabolic disorders and monogenic diseases. 4 In their cohort of 45 children with indeterminate PALF, Hegarty et al 9 reported that next generation sequencing helped identifying specific etiologies in 20% of the cases.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 4 more Smart Citations
“…Although not generally considered as part of the first-line workup for acute liver failure, molecular testing is essential to confirm certain diagnoses in the pediatric population. 8,9 DNA sequencing technology (e.g., clinical exome sequencing and next generation sequencing) is increasingly effective in detecting inherited metabolic disorders and monogenic diseases. 4 In their cohort of 45 children with indeterminate PALF, Hegarty et al 9 reported that next generation sequencing helped identifying specific etiologies in 20% of the cases.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…1,4 Potential causes for indeterminate PALF include occult acetaminophen toxicity, unrecognized viral infection, undiagnosed autoimmune hepatitis and metabolic disorders. 5,9 Alonso et al 85 reported the presence of acetaminophen protein adducts in 11% of patients with indeterminate PALF. 85 Recent studies suggest that many of patients with indeterminate PALF develop hepatic injury due to hyperinflammatory responses and immune dysregulation.…”
Section: Non-hepatotropic Virus Infectionmentioning
confidence: 99%
See 3 more Smart Citations